Trade Openness, Industrialization, Urbanization and Pollution Emissions in GCC countries: A Way Towards Green and Circular Economies - Mahmood, Haider (International Journal of Energy Economics and Policy, 2022)
The GCC countries are moving toward circular and green economies in their long-run visions. This transformation is accelerating the industrialization, urbanization, economic growth, and Trade Openness (TO) in the region. This present study examines the effects of these economic indicators on pollution emissions in the GCC panel from 1980-2019 using panel techniques. We found the environmental Kuznets curve. Moreover, TO is helping reduce CO2 emissions. Hence, economic growth and TO are helping the GCC region to follow the track of green and circular economies. In short run, TO also reduces emissions. Industrialization and urbanization accelerate emissions in long run. Thus, both indicators have environmental consequences in the GCC region in the long run. However, these indicators could not harm the in short run. To follow the track of green and circular economies, the study recommends increasing trade openness in the region and imposing carbon taxes on industrialization and urbanization to reduce their environmental consequences.